A comparative syrup cellular penetration and histological study of three osmotic dehydration procedures of dehydrated mango - Fernandez, Cybelle Marie O.; De Leon, Sonia Y. (1993)
Three osmotic dehydration procedures were carried out in three procedures: in the 40-50-60 Bx step-up process, in the 70 Brix direct immersion process and in th sorbitol-sucrose moist-infusion process befor the final cabinet drying in the production of dehydrated candied mangoes. Solid uptake-water loss behavior was determined for the three procedures in Phase II. Highest percentage of moisture-loss was determined in the sorbitol-sucrose process at 63.56% and lowest in the glucose-sucrose process at 60.32%. Solids gain was highest in the sorbitol-sucrose process at 49.5% and lowest in the step-up process at 35.2%. Weight loss was highest in the sorbitol-sucrose process at 41.35% and lowest in the glucose-sucrose process at 20.51%. Syrup penetration was determined in Phase II and the deepest penetration was found in the step-up process, followed by the glucose-sucrose process and lastly, in the sorbitol-sucrose process. Severe cellular damages were found in the glucose-sucrose and in the sorbitol-sucrose solutions soaked tissues as determined in Phase IV. The least cell damaged were the tissues osmotically dehydrated with the 4.-5.-60 Brix step-up method. Statistical analysis of the sensory evaluation of the final products showed that the step-up processed sample was different from the other two samples and was ranked highest in texture and in general acceptability as determined in Phase 1.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango, Dried; Fruit -- Preservation